The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/909134
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Pattern of T Lymphocytes in AcuteSchistosomiasis mansoniPatients following Treated Praziquantel Therapy

Abstract: Acute schistosomiasis is associated with a primary exposure and is more commonly seen in nonimmune individuals traveling through endemic regions. In this study, we have focused on the cytokine profile of T lymphocytes evaluated in circulating leukocytes of acute Schistosomiasis mansoni-infected patients (ACT group) before and after praziquantel treatment (ACT-TR group). Our data demonstrated increased values of total leukocytes, eosinophils, and monocytes in both groups. Interestingly, we have observed that pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…Their initial expression before treatment was important in helping to mount a humoral response to the infection. However, this contrasts with a previous study [ 31 ], which showed that one month after treatment with praziquantel there was an increase in the production of IL-4 and IL-10 cytokines following SEA stimulation in circulating lymphocytes from infected patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Their initial expression before treatment was important in helping to mount a humoral response to the infection. However, this contrasts with a previous study [ 31 ], which showed that one month after treatment with praziquantel there was an increase in the production of IL-4 and IL-10 cytokines following SEA stimulation in circulating lymphocytes from infected patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The higher than baseline levels of IFN‐γ production in response to SEA observed in egg‐negative children in the post‐MDA group suggests that SEA stimulation of IFN‐γ may be immunoregulated in untreated infections, and that multiple MDAs removed this regulation. Higher SEA‐stimulated IFN‐γ levels have mainly been reported in people with acute schistosomiasis, prior to the development of the regulation associated with chronic infection . Wilson et al also reported a treatment‐associated increase in IFN‐γ, although this increase was only seen 1 year after treatment and was not sustained at 2 years post‐treatment.…”
Section: Discussionmentioning
confidence: 97%
“…If this is confirmed in future studies, then the HTX method would represent the best method for obtaining a precise determination of infection status by egg detection. This determination is particularly critical for vaccine efficacy evaluations, individual clinical diagnoses, and control of cure efforts, especially in non-endemic countries [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%